A State‐of‐the‐Art Review of Laser‐Assisted Bioprinting and its Future Research Trends. Issue 5 (26th June 2021) - Dou, Chaoran; Perez, Victoria; Qu, Jie; Tsin, Andrew; Xu, Ben; Li, Jianzhi
Abstract: Bioprinting is an additive manufacturing technology with great potential in medical applications. Among available bioprinting techniques, laser‐assisted bioprinting (LAB) is a promising technique due to its high resolution, high cell viability, and the capability to deposit high‐viscousity bioink. These characteristics allow the LAB technology to control cells precisely to reconstruct living organs. Recent developments of LAB technologies are reviewed in this paper, covering various designs of LAB printers, research progresses in energy‐absorbing layer (EAL), the physical phenomenon that triggers the printing process in terms of bubble formation and jet development, printing process parameters, and major factors related to the post‐printing cell viability. The latest studies on LAB technologies are highlighted, expounding their advantages and disadvantages, and some potential applications are presented. The potential technical challenges and future research trends for LAB technologies are also discussed. Abstract : Due to its high cell viability and resolution as well as the capability to deposit highly viscous bioink, laser‐assisted bioprinting is a promising technique with great potential especially in medical applications. Recent developments and latest studies on this technology are reviewed, and some potential applications together with technical challenges and future research trends are discussed.